WRESTLING PREPARATION PROCESS IN SPORTS SCHOOLS - Khushmurodov , Bekzod Abduraimovich (Innovative Development in Educational Activities, 2023)
In this article, a survey was conducted on the problems of maintaining a contingent of children involved in freestyle wrestling in sports schools.